Exhaustivo control por los miembros de la fuerza pública al interior de los centros penitenciarios, para decomiso de objetos no permitidos - Jiménez Jiménez, Lidia Vanessa (2022)
The present degree thesis is entitled: "Exhaustive control by members of the public force inside prisons, for confiscation of unauthorized objects", its main interest is to carry out a legal study and an investigation about the existing problem in the improper ingress of unauthorized objects into social rehabilitation centers, a fact that has become one of the main causes that promote violent scenes between people deprived of their liberty. Among the main causes that trigger this series of conflicts and irregularities is the mismanagement in the administration of the penitentiary system by the authorities that do not carry out the necessary controls and seizures due to such case, which facilitates the entry of prohibited objects inside the prisons. Among the most common prohibited objects that can be located inside penitentiaries are: cell phones that are used by inmates as a communication tool in order to keep in touch with their accomplices and colleagues from criminal organizations, in the same way it happens with the entry of different types of weapons that later in the hands of those deprived of liberty are used to cause damage, injury and even lead to the death of their own cellmates and pavilions of the place, the entry of narcotic substances is another of the problems that affect the stability of the center. Within the present thesis work, materials and methods were used that allowed the development of legal research, in the same way, surveys and interviews with legal professionals were raised, the results of which served to propose the project of legal reform to the Comprehensive Criminal Organic Code with the purpose to amend article 685 of the Organic Comprehensive Criminal Code, which will consist of the following: Art. 685. Internal and perimeter security of the deprivation of liberty centers. - The internal security of the deprivation of liberty centers is the responsibility of the prison security force and the National Police. Perimeter security is the unique and exclusive competence of the National Police and Armed Forces.